(untitled) (Journal of Pathology of Nepal, 2023)
Background: Ovarian tumors are a common form of neoplasm in women. Early diagnosis and management of ovarian tumors is a major problem in a developing country like Nepal, due to lack of awareness and limited facility for investigations in all parts of Nepal. Usually, the malignant ovarian neoplasms will have already advanced too far by the time they are detected. This study was proposed to identify the spectrum of ovarian tumors and their clinicopathological features. Materials and methods: This was a hospital-based cross-sectional descriptive study over a period of two years. Ovarian tissue with clinical notes sent to the histopathology department in 10% formalin was received. The specimens were subjected to critical gross as well as histopathological study. Routine paraffin sections with Hematoxylin & Eosin staining were used. The clinical as well as histological findings were compiled on proforma and then subjected to analysis. This was a descriptive study and data were tabulated and analyzed using the Statistical Package for Social Sciences (SPSS) version 21.0 Results: A total of 50 patients were included in the study with the age range from 15 years to 63 years. Maximum patients were from age group 41-50 years (36%). In the present study, abdominal pain (62%) was the most common presenting complaint followed by mass per abdomen (20%) and irregular periods (10%). The majority of the ovarian tumors belonged to benign tumors (82%) followed by malignant tumors (12%). As per WHO classification, surface epithelium tumors were found to be the most common variety (84%), followed by germ cell tumors (10%). Among the various known subtypes of ovarian tumors, serous cystadenoma (48%) was found to be the most common subtype followed by mucinous cystadenoma (20%). Conclusions: Benign ovarian tumors are more common than malignant or borderline tumors. Among the histopathological subtypes of ovarian tumors, surface epithelial tumors are the most common type. Differentiation between benign and malignant tumors is important to assure proper management and recovery. Similar studies with greater sample size are advisable in the future.